Towards the production of carrier-free 99Mo by neutron activation of 98Mo in molybdenum hexacarbonyl –Szilard-Chalmers enrichment. (October 2018) - van Dorp, Jan Willem J.; Mahes, Dravin S.; Bode, Peter; Wolterbeek, Hubert T.; Denkova, Antonia G.; Serra-Crespo, Pablo
Abstract: The neutron irradiation of molybdenum hexacarbonyl has been systematically studied to identify possible improvements for the production of molybdenum-99. After irradiation, the targets were dissolved in dichloromethane, and Szilard-Chalmers liquid-liquid extraction was carried out with aqueous extractants. The effects of the irradiation time, the aqueous phase composition and the irradiated mass were studied with a focus on the chemistry involved. Stable extraction yields of 20% were obtained with enrichment decreasing with target decomposition. Improved enrichment requires decreased decomposition. Highlights: 99 Mo yield depends on recombination processes and the extractant. 98 Mo mass transfer depends on target decomposition, concentration and the extractant. Enrichment depends mainly on the target decomposition.